Analysis of neutron-rich isotopes around the Z-38 region populated through a heavy-ion fission reaction (2014)
Abstract. The study of neutron-rich nuclei is currently one of the most active research fields in nuclear physics. The neutron excess that these nuclei contain in comparison to the stable nuclei induces new physics phenomena such as changes of the so called magic numbers given by the nuclear shell model, which leads to unexpected deformations of the nuclear shape of these nuclei far away from the stability line. In the last decades, neutron-rich nuclei with a number of protons (Z) near 38 have gained attention due to the evolution of their nuclear deformation as a function of the number of neutrons. The most remarkable case corresponds to Zirconium (Z=40), where the nuclear deformation changes from a quasi-spherical shape for 96Zr, to a highly prolate deformation as in the case of 104Zr. Nevertheless, the experimental study of this behaviour has not been completed yet since the low production cross-section of these isotopes demands improved facilities only recently developed, with a detection eficiency high enough to clearly detect these nuclei together with the gamma radiation emmited by them when de-excite. In 2011, at the Laboratori Nazionali di Legnaro, Italy, neutron-rich nuclei in the Z-38 region were populated by the fission reaction of a 136Xe projectile colliding against a 238U target, at a beam energy of 960 MeV. In order to detect the nuclear species produced and the gamma rays emmited by them, the new -ray detector AGATA Demonstrator was used in coupling with the mass spectrometer PRISMA. In this thesis the data obtained has been analysed in order to determine the mass distribution for the detected neutron-rich Zirconium and Strontium isotopes together with their associated gamma spectrum.